Dimensiones e indicadores para el estudio del desempeño profesional pedagógico del tutor de práctica pre profesional - Mazorra Fuentes, Onixa de la Caridad (2017)
Today’s society sets heavy demands on the formation at the undergraduate level and for the production and service sectors, it requires a professional performance from the practicum advisors which may provide a response to the requirements considered in the exit profile of the different technical careers. The professional performance of the practicum advisors is the main issue in this article in which the theoretical research done on the topic is presented. This allowed the author to take a position (point of view) based on the theory reviewed; especially, on essentia terminology such as performance, professional performance, professional pedagogical performance, and professional pedagogical performance from practicum advisors. Three main elements of this performance are described: (1) formative-evaluative, (2) technical-pedagogical-professional, and (3) personal growth, which go in hand with the present demands of production and services from which the dimensions and indicators for this study are derived. This article’s main objective is to present to the reader a summary of the literature reviewed about the related terminology as well as an explanation of the methodological process employed for determining the dimensions and indicators implicit in the professional pedagogical performance from the practicum advisors, and the results obtained. For this purpose, a theoretical methodology was employed such as the analysis, synthesis, generalization, and abstraction for the study. The result is a systematization of the professional pedagogical performance and professional pedagogical performance from the practicum advisors defined as well as the operationalization of this variable and its indicators.